PROGNOSTIC SIGNIFICANCE OF IMMUNOGENETIC MARKERS IN THE EARLY ASSESSMENT OF DECOMPENSATION RISK IN LIVER CIRRHOSIS - Rasulov , Boburjon; Ravzatov , Jasurbek (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Liver cirrhosis is the terminal stage of chronic liver disease, and its prognosis is largely determined by the development of decompensation phenotypes. Complications such as ascites, variceal bleeding, spontaneous bacterial peritonitis, and hepatic encephalopathy markedly worsen patient survival. In recent years, systemic inflammation, disruption of the gut-liver immune axis, and cytokine imbalance have been recognized as major contributors to the clinical course of cirrhosis. In particular, the Th17/IL-23/IL-17 signaling pathway and the IL-6 cascade are increasingly regarded as factors associated with fibrosis progression, infectious complications, and adverse outcomes. This thesis highlights the prognostic significance of immunogenetic markers, including IL-23R, IL-17A, IL-17F, and IL-6, for early assessment of decompensation risk in liver cirrhosis. The integration of molecular-genetic indicators with conventional clinical criteria represents a promising strategy for personalized prognosis and risk stratification.